2016
DOI: 10.1177/229255031602400209
|View full text |Cite
|
Sign up to set email alerts
|

Late postoperative massive bleeding in septorhinoplasty: A prospective study

Abstract: Late bleeding in septorhinoplasty is rare. It may be prevented by completely filling the nasal cavity so that there is no dead space between the septal mucosal membranes and the drainage opening. If bleeding occurs, it can be treated by placement of a tampon soaked in adrenalin and tranexamic acid plus intravenous administration of 250 mg tranexamic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…21 However, owing to its rebounding activity and systemic cardiovascular side effects such as tachycardia, it can be used sparingly. 22 In our research, hemodynamic changes such as heart rate and systolic blood pressure were not observed following surgery. Also, in the current study, no side effects were observed due to increasing the dose of epinephrine, and also considering the cheapness and availability of this drug in terms of cost-effectiveness, it seems reasonable to use a higher dose of this drug depending on the surgeon.…”
Section: Discussionmentioning
confidence: 48%
“…21 However, owing to its rebounding activity and systemic cardiovascular side effects such as tachycardia, it can be used sparingly. 22 In our research, hemodynamic changes such as heart rate and systolic blood pressure were not observed following surgery. Also, in the current study, no side effects were observed due to increasing the dose of epinephrine, and also considering the cheapness and availability of this drug in terms of cost-effectiveness, it seems reasonable to use a higher dose of this drug depending on the surgeon.…”
Section: Discussionmentioning
confidence: 48%
“…In our review, 23 studies assessed the use of TXA in various aesthetic or breast-related procedures [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. [57,59,60], and one was a case series [52]. Study sample ranged from 20 to 304 patients, apart from a single cohort study of 750 septo-rhinoplasty patients [57].…”
Section: Aesthetic Surgery/breast Surgerymentioning
confidence: 99%
“…[57,59,60], and one was a case series [52]. Study sample ranged from 20 to 304 patients, apart from a single cohort study of 750 septo-rhinoplasty patients [57].…”
Section: Aesthetic Surgery/breast Surgerymentioning
confidence: 99%
See 2 more Smart Citations